Beta Diversity of Antarctic and Sub-Antarctic Benthic Communities Reveals a Major Role of Stochastic Assembly Processes - Valdivia, Nelson; Garcés-Vargas, José; Garrido, Ignacio; Gómez, Iván; Huovinen, Pirjo; Navarro, Nelso P.; Macaya, Erasmo C.; Pardo, Luis Miguel (Frontiers in Marine Science, 2021)
Community assembly is the result of both, deterministic and stochastic processes. The former encompasses niche-based local-scale mechanisms such as environmental filtering and biotic interactions; the latter includes ecological drift, probabilistic colonisation, and random extinctions. Using standardised sampling protocols, we show that the spatial variation in community composition (beta diversity) of subtidal macrobenthic rocky communities of sub-Antarctic and Antarctic localities reflects a high contribution of stochastic processes to community assembly. Localities were Strait of Magellan, Yendegaia Fjord (Beagle Channel), and Fildes Bay (King George Island, West Antarctic Peninsula). Null model analyses indicated that random sampling from species pools of different sizes drove the observed among-locality differences in incidence- and abundance-based beta diversity. We analysed a normalised stochasticity ratio (NST), which delimits between more deterministic (< 50 %) and more stochastic (> 50 %) assembly. NST was notably larger than 50 %, with mean values of 69.5 % (95 % CI = 69.2 - 69.8 %), 62.5 % (62.1 - 62.9 %), and 72.8 % (72.5 – 73.2 %) in Strait of Magellan, Yendegaia Fjord, and Fildes Bay, respectively. Accordingly, environmental factors, such as depth, substrate composition, seawater temperature, salinity, and light penetration, accounted for a small fraction of the spatial variation in community composition across the three localities. In this region, therefore, stochasticity and processes influencing species pool sizes (e.g., macroevolutionary dynamics) could have stronger effects on community assembly than deterministic niche-based factors. As anthropogenic biotic homogenisation continues apace, our study can give useful insights into the major ecological processes in Southern Ocean’ coastal marine communities.